Examining mediating role of Environmental Performance and Green Purchasing between Green Eco Design and Green Information Systems with Performance, Supported Renewable Energy - Muhammad Ikhsan Setiawan; Dahlan Abdullah; Veronika Nugraheni Sri Lestari; Yuniningsih . (International Journal of Supply Chain Management, 2019)
Overview – Mining sector of Indonesia is very Important and contributes a lot in the GDP of the economy. It is important for mining industry to improve their financial performance along with improving environmental performance. Purpose–The aim of current study is to investigate the impact of eco-design and environmental performance on organizational performance. Moreover, the study has examined the impact of green information system and green packaging towards organizational performance.Analysis approach – For this study we have used the survey-based method for data collection and the questionnaire was collected from 500 target population. Partial least square (PLS) method is used for data examining and providing empirical support for the developed hypotheses. Findings – The research findings have proved that all of the proposed hypothesis have shown significant results. Research implications – The study has several implications as it provides literature based on empirical evidence regarding the high influence of green sustainable practices on the ultimate performance goal of organizations.